E-GOVERNMENT DALAM BUSINESS PROCESS REENGINERING ADMINISTRASI PELAYANAN PERIZINAN - Harahap, Agus Supriadi (Fakultas Politik Pemerintahan, 2018)
ABSTRACT Depok is a city that is directly adjacent to the State Capital Jakarta. We know the city very narrow and very expensive housing land, the people’s choice is certainly suburb of the city that faced Depok. People in the sense of disappointment in the management of IMB, ranging from problems of slow and obscurity until the problem. convoluted procedure is coupled with process information that is not clear and always float, eventually the certainty of always not found. This research conducted with qualitative methods, collecting data through interviews, observation and in-depth discussions with informants who are directly related to the issuance of IMB service process, from the entire city of Depok regional organizations involved in the publishing process IMB. The results showed that the application of Electronic Government in the process of publishing Building Permit (IMB) in Depok in West Java has not applied thoroughly and with a system that has not integration. Implementation of Electronic Government in the work units involved in the process of IMB also yet thoroughly and also not maximized in the improvement of work processes (Business Process reengineer). Information Technology applications and infrastructure used in the process of issuing building permit was not optimal in helping the process of IMB. This study also shows the weakness of the role and functions of the organization which accountability in the application of information technology, lack of commitment in the implementation of electronic government, the difficulty of doing business systems integration services network IMB). Keywords: electronic government, business process reengineer.